PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MASALAH KONTEKSTUAL SISWA KELAS X SMA NEGERI 2 MALINAU - YULIANA YULIANA (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2023)
This research is a classroom action research that aims to improve students' mathematics learning outcomes through problem-based learning based on contextual problems in the material of a system of three-variable linear equations. This research was conducted at SMA Negeri 2 Malinau for the 2021/2022 academic year with the research subjects being class X students and the object of the research being the application of problem-based learning. This research consists of two cycles. Data collection techniques were carried out through documentation of initial ability scores, observations, and learning achievement tests. Observations carried out at each meeting during the learning process took place including observations of the activities of teachers and students. Learning outcomes test is given at the end of each cycle. In addition, it also takes into account the value of assignments during the learning process. The results of the research in the first cycle showed that the average value of student learning outcomes increased by 58.88% from the basic value of 41.96 to 66.74. In cycle II, the average value of student learning outcomes increased by 22.23% from the value of learning outcomes in cycle I, namely 66.74 to 81.58. The teacher's activities in the first cycle were sufficient and in the second cycle they were good. Student activity in cycle I was classified as lacking and in cycle II was classified as good. Based on the results of data analysis, it can be concluded that the problem-based learning model based on contextual problems can improve mathematics learning outcomes in the material of the three-variable linear equation system for class X SMA Negeri 2 Malinau Academic Year 2021/2022. ABSTRAK Penelitian ini merupakan penelitian tindakan kelas yang bertujuan untuk meningkatkan hasil belajar matematika siswa melalui pembelajaran problem based learning berbasis masalah kontekstual pada materi sistem persamaan linear tiga variabel. Penelitian ini dilaksanakan di SMA Negeri 2 Malinau tahun ajaran 2021/2022 dengan subjek penelitian adalah siswa kelas X dan objek penelitian adalah penerapan pembelajaran problem based learning. Penelitian ini terdiri dari dua siklus. Teknik pengumpulan data yang dilakukan melalui dokumentasi nilai kemampuan awal, observasi, dan tes hasil belajar. Observasi dilaksanakan pada setiap pertemuan selama proses pembelajaran berlangsung meliputi observasi terhadap aktivitas guru dan siswa. Tes hasil belajar diberikan pada setiap akhir siklus. Selain itu juga memperhitungkan nilai tugas selama proses pembelajaran. Hasil penelitian pada siklus I menunjukkan rata-rata nilai hasil belajar siswa meningkat sebesar 58,88% dari nilai dasar yaitu 41,96 menjadi 66,74. Pada siklus II, nilai rata-rata hasil belajar siswa meningkat sebesar 22,23% dari nilai hasil belajar siklus I yaitu 66,74 menjadi 81,58. Aktivitas guru pada siklus I tergolong cukup dan pada siklus II tergolong baik. Aktivitas siswa pada siklus I tergolong kurang dan pada siklus II tergolong baik. Berdasarkan hasil analisa data, maka dapat disimpulkan bahwa model pembelajaran problem based learning berbasis masalah kontekstual dapat meningkatkan hasil belajar matematika pada materi sistem persamaan linear tiga variabel siswa kelas X SMA Negeri 2 Malinau Tahun Ajaran 2021/2022.